Mitochondria: An Organelle of Bacterial Origin Controlling Inflammation - Meyer, Alain; Laverny, Gilles; Bernardi, Livio; Charles, Anne Laure; Alsaleh, Ghada; Pottecher, Julien; Sibilia, Jean; Geny, Bernard (Frontiers in Immunology, 2018)
Inflammation is a cellular and molecular response to infection and/or tissues injury. While a suited inflammatory response in intensity and time allows for killing pathogens, clearing necrotic tissue and healing injury; an excessive inflammatory response drives various diseases in which inflammation and tissues damages/stress self-sustain each other. Microbes have been poorly implied in non-resolving inflammation, emphasizing the importance of endogenous regulation of inflammation. Mitochondria have been historically identified as the main source of cellular energy, by coupling the oxidation of fatty acids and pyruvate with the production of high amount of ATP by the electron transport chain. Mitochondria are also the main source of reactive oxygen species. Interestingly, research in the last decade has highlighted that since its integration in eukaryote cells, this organelle of bacterial origin has not only been tolerated by immunity, but has also been placed as a central regulator of cell defense. In intact cells, mitochondria regulate cell responses to critical innate immune receptors engagement. Downstream intracellular signaling pathways interact with mitochondrial proteins and are tuned by mitochondrial functioning. Moreover, upon cell stress or damages, mitochondrial components are released into the cytoplasm or the extra cellular milieu, where they act as danger signals when recognized by innate immune receptors. Finally, by regulating the energetic state of immunological synapse between dendritic cells and lymphocytes, mitochondria regulate the inflammation fate towards immunotolerance or immunogenicity. As dysregulations of these processes have been recently involved in various diseases, the identification of the underlying mechanisms might open new avenues to modulate inflammation.